Computerized tomography scan and head injury: the experience in a tertiary hospitl in nigeria. A cross sectional study (2015)
Trauma is the leading cause of death in all age groups, and head trauma is the cause of death in more than 50% of cases. Head injury reduces the level of physical and mental health of a community, ultimately increasing the socioeconomic burden. In our resource limited country, skull x ray was the main mode of investigating head trauma until recently when computerized tomography (CT) scans became the modality of choice in the initial work up of patients. In this study, we sought to document the various post traumatic CT scan findings following head injury in a tertiary hospital in Lagos and determine the sociodemograhic and radiological characterostic such patients. This was a descriptive, prospective, cross- sectional study of the CT scan findings of 400 cases with acute head trauma, from June 2010 to October 2011. The mean age of the participants was 32.7+ 18.2 years with a male to female ratio of 2.5:1. Majority, 65.5% of the study subjects had positive CT findings while the remaining, 34.5% had normal CT findinfs. Raod traffic accident(RTA) was found to be the most common cause of head injury, occuring in 69% cases, especially in the 21 to 30 years age group. Cerebral contusions, 35.5% and skull fractures, 34.3% were the most common lesions found while foreign body, 1.5% were the least. This study confirmed the versatility of CT scan in detecting both intracranial and extra cranial lesions in patients with head injury from RTA, which is the most common cause, while the most frequent lesion was cerebral constusion.